Renewable and Sustainable Green Diesel (D100) for Achieving Net Zero Emission in Indonesia Transportation Sector - Indra Chandra Setiawan; Muji Setiyo (Universitas Muhammadiyah Magelang, 2022)
Because of the significant demand for fuels in the transportation sector in Indonesia, as well as concerns about energy security and global warming, renewable, sustainable, and alternative energy sources such as biofuels are required to replace petroleum-based fuels. Promoting the production of green diesel from crude palm oil (CPO) using palm fatty acid distillate (PFAD) as its byproduct will make the overall process more efficient and environmentally friendly in Indonesia. As a result, CPO-based diesel production will be a green and high-value sector. By replacing fossil diesel with green diesel, a sustainable energy source can be assured without further depleting current fossil fuels, leading to cleaner and greener energy in the future and meeting the net-zero aim by 2060.